واقع الثقافة البيئية في المجتمع الحضري - مخيبر، فوزي (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة: تهدف هذه الد ارسة للتعرف على واقع الثقافة البیئیة في المجتمع الحضري لمدينة الوادي وذلك للمشاكل البیئیة التي طغت على الوسط الحضري وانتشار الملوثات داخل أحیائه، وللتعرف على واقع الثقافة البیئیة في المجتمع الحضري تم طرح التساؤل التالي: ما هو واقع الثقافة البيئية في المجتمع الحضري؟ واندرجت تحت التساؤل الرئیسي ثلاثة تساؤلات فرعیة: -1ما هي أبرز مظاهر التلوث الحضري؟ -2ما هي علاقة السكان بوسطهم البیئي؟ -3ما مدى مساهمة السكان في مواجهة المشكلات البیئیة؟ اعتمدنا في هذه الدراسة على المنهج الوصفي وعلى عینة قصدیة ممثلة لمجتمع الدراسة قدرها 100شاب من الحي، كما طبقنا الاستبیان كأداة لجمع البیانات من أفراد العینة، وفي الأخیر تمت معالجة البیانات إحصائیا بالتكرارات والنسب المئویة لنصل في النهایة للنتائج التالیة: - أن تدهور بیئة الحي وانتشار النفایات في شوارعه مرده في الدرجة الأولى للسكان فهم السبب الرئیسي في نشر التلوث داخله وذلك لانتشار النفایات المنزلیة التي تشوهه وعدم مساهمتهم في التخلص منها وذلك لعدم وعیهم بالسلوك السلبي الذي یقومون به تجاه بیئتهم وذلك في غیاب الثقافة والوعي البیئي الذي یحدد ویضبط سلوكیاتهم تجاهها. - أن علاقة السكان ببیئتهم الحضریة مقتصرة حول المناطق القریبة من منازلهم، وهذا يدل على الإهمال البیئي للوسط الذي یعیشون فیه وأن مساهمتهم الفردیة منها أو الجماعیة ضعیف إذ تعلق الامر بمشكلات البیئة في الوسط العام. - أن عدم اطلاع الافراد للمواضیع التي تخص البیئة والتغاضي عنها يزید من احتمالیة تلوث الوسط الحضري وذلك لافتقارهم المعرفة الكافیة والقیم البیئیة والتي هي بمثابة الموجهات لسلوكهم ونشاطهم نحو البیئة. - أن الاف ارد لا يولون للجانب القانوني أهمیة في حالة تعرض الوسط البیئي للتلویث من قبل السكان بل یكتفون بالنصح للحفاظ على العلاقات وهذا على حساب البیئة.- أن غیاب الوعي البیئي والذي من شأنه وضع المجتمع الحضري في وضع بیئي حرج مرده غیاب عملیات التحسیس التي من المفترض أن تقدمها الجمعیات وتسعى لتحقیقها ونشر الثقافة البیئیة في الوسط الحضري والنهوض بالمجتمع من الحالة البیئیة التي وصل الیها.Summary of the study The current study aims to identify the reality of environmental culture in the urban society of El-oued. The motive behind this study is the environmental problems that overwhelmed this society and the spreading of pollutants within its neighborhood. In order to identify the reality of environmental culture in urban society, the following question is raised : To what extent does the environmental culture widespread in EL-oued city ? Three sub-questions are asked : 1- What are the most prominent aspects of pollution in the neighborhood ? 2. What is the relationship between the residents of the neighborhood and their environment ? 3. What is the extent to which residents of the neighborhood contribute to environmental problems ? In this study, we adopted the descriptive approach. The representative sample of the study population is 100 young people from the neighborhood. In addition, we applied the questionnaire as a tool for collecting data from the sample. Data were statistically processed using frequency and percentages. Thus, the study have shown the following results : - Environment deterioration is primarily due to humans (inhabitants) since they are the main reason for pollution and household waste spreading. Because of the lack awareness of the negative behavior they do towards their environment, in the absence of culture and environmental awareness, they spread the household waste but they do not seek to disposal. - Inhabitants' relationship with their urban environment is limited to the areas close to their homes, This indicates their ignorance of the environment where they live., and that their individual or collective contribution is weak as it relates to environmental problems. - Lack of knowledge related to environmental issues by individuals may increase the contamination of the urban environment because of their lack of sufficient knowledge and environmental values, which serve as guidelines for their behavior and activity towards the environment.- Individuals do not care about the legal aspect in the case when the environment is exposed to pollution by individuals. However, they just advise to maintain relations at the expense of the environment. - The absence of environmental awareness is due to the absence of sensitization processes that are supposed to be provided by the associations. These associations seek to disseminate environmental culture in the urban environment
دراسة ميدانية لمواقف عينة من شباب حي الحرية
مذكرة ماستر علوم اجتماعية تخصص علم الاجتماع الحضري
Keywords: الثقافة البيئية، المجتمع الحضري، البيئة والإنسان